Epistemologi Manusia Sebagai Khalifah Di Alam Semesta - Salamah Eka Susanti (Institut Ilmu Keislaman Zainul Hasan Genggong, 2020)
In much literature that discusses the existence of humans in the universe is always associated with the concept of human caliphate on earth and the concept of worship. The position of humans in the universe that is mandated as Khalifatullah Fi al-Ardh has a moral responsibility in carrying out the function of the caliphate. The relationship between humans and the universe, including human relationships with other humans, is not a relationship between the ruler and the mastered, but a relationship that has the same goal that is worth worship, namely obedience to God. Because even if humans are able to master, but it is not because of the strength they have, but it is caused by God who subdues it to humans. That is, leadership and human power must still be placed within the framework of human existence that is temporary, so that the tendency of leadership or power can be avoided, which can consequently damage the order of life.